A single amino acid residue regulates PTEN-binding and stability of the spinal muscular atrophy protein SMN - Rademacher, S; Detering, NT; Schüning, T; Lindner, R; Santonicola, P; Wefel, I-M; Dehus, J; Walter, LM; Brinkmann, H; Niewienda, A; Janek, K; Varela, MA; et al. (MDPI, 2020)
Spinal Muscular Atrophy (SMA) is a neuromuscular disease caused by decreased levels of the survival of motoneuron (SMN) protein. Post-translational mechanisms for regulation of its stability are still elusive. Thus, we aimed to identify regulatory phosphorylation sites that modulate function and stability. Our results show that SMN residues S290 and S292 are phosphorylated, of which SMN pS290 has a detrimental effect on protein stability and nuclear localization. Furthermore, we propose that phosphatase and tensin homolog (PTEN), a novel phosphatase for SMN, counteracts this effect. In light of recent advancements in SMA therapies, a significant need for additional approaches has become apparent. Our study demonstrates S290 as a novel molecular target site to increase the stability of SMN. Characterization of relevant kinases and phosphatases provides not only a new understanding of SMN function, but also constitutes a novel strategy for combinatorial therapeutic approaches to increase the level of SMN in SMA.